2019
DOI: 10.1002/nbm.4055
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of basis functions and q‐space sampling schemes for robust compressed sensing reconstruction accelerating diffusion spectrum imaging

Abstract: Time constraints placed on magnetic resonance imaging often restrict the application of advanced diffusion MRI (dMRI) protocols in clinical practice and in high throughput research studies. Therefore, acquisition strategies for accelerated dMRI have been investigated to allow for the collection of versatile and high quality imaging data, even if stringent scan time limits are imposed. Diffusion spectrum imaging (DSI), an advanced acquisition strategy that allows for a high resolution of intra‐voxel microstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 46 publications
(111 reference statements)
0
11
0
Order By: Relevance
“…This is confirmed since our results were similar to the results obtained in Bilgic et al 19 where they used wavelets and total variation as sparsifying transforms. Furthermore, in Paquette et al 20 and Tobisch et al 36 it is shown that it produces satisfactory reconstruction performance in comparison to other sparsifying transforms or methods based on other continuous basis functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is confirmed since our results were similar to the results obtained in Bilgic et al 19 where they used wavelets and total variation as sparsifying transforms. Furthermore, in Paquette et al 20 and Tobisch et al 36 it is shown that it produces satisfactory reconstruction performance in comparison to other sparsifying transforms or methods based on other continuous basis functions.…”
Section: Discussionmentioning
confidence: 99%
“…Future work could include further propagator-based quality measures, such as the non-Gaussianity 36 and the angular error in crossing angle 36 to complement NMSE, PC, MSD, and p0; to increase the characterization of the propagator reconstruction quantitatively. Finally, this comparison could be improved using recent advances of the corresponding methods, like the Laplacian regularized MAP, 24 joint k-q reconstruction, 37 or the implementation of deep learning for CSD like in Rasmussen et al 38…”
Section: Discussionmentioning
confidence: 99%
“…We use 600 simulations from high‐contrast q ‐space data from 2 90 crossing fibers as in 18 . These simulations have the same microstructure but different orientations in 3D space.…”
Section: Methodsmentioning
confidence: 99%
“…Mean Apparent Propagator (MAP) 16‐22 is a physical model whose basis functions are Gauss‐Hermite functions. The first basis‐function corresponds to Gaussian diffusion as in DTI, and the following basis functions correspond to non‐Gaussian diffusion; hence, it can represent well the complete diffusion propagator.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation